Peri-oral bullous impetigo: a diagnostic dilemma for dentist - Zakaria, A.S.I; Sockalingam, S.N.M.P (Universiti Kebangsaan Malaysia, 2013)
Bullous impetigo is a highly contagious skin infection commonly affecting children due to epidermolytic toxins of bacteria Staphylococcus sp. This presentation described a case of a 3 year-old Indian girl with bullous lesion around the peri-oral region. The lesion was initially thought to be of viral origin and was treated symptomatically. However, the lesion progressed without any resolution with more vesicles at distant sites. The patient was also having fever and refused any oral intake. At this point, a probable diagnosis of bacterial skin infection was considered and the patient was admitted. Intra-venous fluid was administered to rehydrate the patient and she was treated with topical antibiotic and antipyretic. The lesion resolved within 14 days without scarring. As dental practitioners, we should be aware of bacterial infection around the peri-oral region and consider it as part of a differential diagnosis so that an appropriate treatment can be given.